Whole-Blood Tacrolimus Trough Concentration in Renal Transplant Recipients at a Tertiary Care Center in Central Nepal: A Cross-sectional Study - Sharma, Vijay; Niraula, Apeksha; Tuladhar, Eans Tara; Dubey, Raju Kumar; Bhattarai, Aseem; Raut, Mithileshwer; Kadel, Anuradha; Kharal, Nikita; Sapkota, Srijana; Pokhrel, Prakash (Journal of Institute of Medicine Nepal, 2024)
IntroductionTacrolimus, a widely used immunosuppressant for renal transplantation, requires careful monitoring due to its narrow therapeutic index and high pharmacokinetic variability. Hence, this study aimed to evaluate the whole blood tacrolimus trough levels in post-renal transplant patients at TUTH.MethodsA total of 257 patients who had undergone kidney transplantation were included in this descriptive cross-sectional study Whole-blood tacrolimus concentration was measured using the ARCHITECT i1000SR analyzer (Abbott Diagnostics, North Chicago, USA) by CMIA. Ethical approval was taken from the Institutional Review Committee of TUTH [Ref. No.: 448(6-11) E2081/082].ResultsAmong the 257 renal transplant recipients, 197(76.65%) were male and 60(23.35%) were female, with a mean age of 38.06±10.74 years. The mean tacrolimus trough level was 7.58±3.92 ng/mL, with a median of 6.8(IQR: 5.4- 9.1) ng/ml. Females had a slightly higher median tacrolimus concentration [7.2(IQR: 5.7- 9.1)] compared to males [6.8(IQR: 5.7- 9.1)]. Of the determinations, 175(68.09%) were within the therapeutic range (5-15 ng/mL), 68(26.46%) were below it, and 14(5.45%) had elevated tacrolimus levels.ConclusionsThe median tacrolimus trough level in this study was 6.8 ng/mL (IQR: 5.4–9.1), slightly higher but within the therapeutic range compared to similar studies done in similar settings. Monitoring of tacrolimus trough concentrations is of utmost importance in the management of kidney transplant recipients.